Revitalisation as a force promoting spatial changes in Wrocław = Idea rewitalizacji motorem przemian przestrzennych Wrocławia - Kożan, Aldona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The idea of revitalization, which grew out of the need to repair degraded urban spaces, has taken on a new meaning in the context of contemporary development challenges. The work includes references to the basic programme documents and strategies.
Keywords: Wrocław; strategia; program rewitalizacyjny; obiekty Euro 2012; przestrzeń publiczna; obiekt kultury; kampus uczelni; strategy; revitalisation programm; investments for Euro 2012; public space